PML-driven sumoylation of PML::RARA-bound repressors drives hematopoietic progenitor immortalization - Hsin Chieh Wu; Emmanuel Laplantine; Cécile Esnault; Michiko Niwa-Kawakita; Yi Zhang; Viviane De Almeida Bastos; Marie-Claude Geoffroy; Hugues de Thé (Journal of Experimental Medicine, 2026)
While acute promyelocytic leukemia (APL) is always driven by fusions involving one of the three retinoic acid receptors, why PML and RARA are the preferred fusion partners has remained largely unsettled. Here, we demonstrate that corepressor (NCoR) binding onto the RARA moiety of PML::RARA is required for hematopoietic progenitor immortalization. We establish that PML-mediated tethering of the UBC9 SUMO-conjugating enzyme onto PML::RARA enforces SUMO2 conjugation of multiple RARA partner proteins, notably the NCoR complex, boosting its repressive power. PML mutants that fail to recruit UBC9 yield PML::RARA fusions that promote neither NCoR sumoylation nor transformation. Conversely, direct UBC9/RARA fusion drives both efficient corepressor complex sumoylation and immortalization. Sumoylation inhibitors reactivate retinoic acid target genes in PML::RARA-expressing, but not in RARA-expressing, progenitors and trigger APL differentiation. Thus, fusion of PML to RARA entails an unexpected gain of function that boosts RARA-mediated transcriptional repression through sumoylation of PML::RARA-bound proteins, explaining the recurrent implication of PML and RARA in APL pathogenesis.